The future of the circular economy and its effect on supply chain dependencies: Empirical evidence from a Delphi study - Gebhardt, Maximilian; Spieske, Alexander; Birkel, Hendrik (Transportation Research Part E-Logistics and Transportation Review, 2022)
This paper conducts a Delphi study to empirically explore the future roadmap of the circular economy (CE). Moreover, we build on the resource dependence theory to explore the CE’s potential to reduce dependencies in supply chain (SC) networks. Based on current literature, the CE practices of the 4R framework (reduce, reuse, recycle, recover), and a series of workshops, we formulated 11 future-oriented projections. In two subsequent Delphi rounds, 78 international CE and SC management experts quantitatively assessed the projections regarding their probability of occurrence in 2030, their potential to reduce SC dependencies, and their desirability. A fuzzy c-means algorithm was applied to cluster the projections based on the expert assessments. We found that the implementation likelihood of CE practices in 2030 is not congruent with the value retention hierarchy advocated by the 4R framework. Qualitative analyses of the panelists’ written statements revealed that regulation, financial attractiveness, customer demand, technological innovation, and product design are the most prominent influencing factors for the future implementation of various CE practices. Moreover, different practices revealed a varying capacity to reduce SC dependencies. More precisely, we found that diversifying a company’s supply base through recycled materials and components has the highest potential. Our qualitative data further provides evidence that CE practices’ capacity to lift dependencies can become an enabler for SC resilience.
Keywords: Circular economy; Sustainable supply chain management; Supply chain resilience; Delphi study; Resource dependence theory